Mycorrhizal response strategies of trifoliate orange under well-watered, salt stress, and waterlogging stress by regulating leaf aquaporin expression - Cheng, Xiao-Fen; Wu, Hui-Hui; Zou, Ying-Ning; Wu, Qiang-Sheng; Kuča, Kamil (Plant physiology and biochemistry, 2021)
Aquaporins (AQPs) involved in water and small molecule transport respond to environmental stress, while it is not clear how arbuscular mycorrhizal fungi (AMF) regulate AQP expression. Here, we investigated the change in leaf water potential and expression level of four tonoplast intrinsic proteins (TIPs), six plasma membrane intrinsic proteins (PIPs), and four nodin-26 like intrinsic proteins (NIPs) genes in trifoliate orange (Poncirus trifoliata) inoculated with Funneliformis mosseae under well-watered (WW), salt stress (SS), and waterlogging stress (WS). Root AMF colonization and soil hyphal length collectively were reduced by SS and WS. Under WW, inoculation with AMF gave diverse responses of AQPs: six AQPs up-regulated, three AQPs down-regulated, and five AQPs did not change. Such up-regulation of more AQPs under mycorrhization and WW partly accelerated water absorption, thereby, maintaining higher leaf water potential. However, under SS, all the fourteen AQPs were dramatically induced by AMF inoculation, which improved water permeability of membranes and stimulated water transport of the host. Under WS, AMF colonization almost did not induce or even down-regulated these AQPs expressions with three exceptions (PtTIP2;2, PtPIP1;1, and PtNIP1;2), thus, no change in leaf water potential. As a result, mycorrhizal plants under flooding may have an escape mechanism to reduce water absorption. It is concluded that AMF had different strategies in response to environmental stresses (e.g. SS and WS) by regulating leaf AQP expression in the host (e.g. trifoliate orange).
Keywords: Poncirus; voda; Water; Citrus; Symbiosis; Mycorrhizae; Aquaporin; Water stress; mykorhiza; listy rostlin; houby; Aquaporins; Abiotic stress; solný stres; akvaporiny; Salt Stress; Plant Leaves; Fungi